Designing English Lessons for Special Needs Students in Home Education: An Adaptive Approach - Malika Ergasheva (Academicia Globe: Inderscience Research, 2025)
The increasing demand for inclusive education has underscored the need for effective instructional strategies tailored to the diverse needs of learners, particularly those receiving home-based education due to physical, sensory, or cognitive limitations. This study explores the principles and practices of designing English language lessons for special needs students in a home education setting through the implementation of adaptive learning technologies. The research identifies pedagogical frameworks, technological tools, and differentiated instructional strategies that ensure accessibility, engagement, and skill acquisition for learners with varying capabilities. The adaptive approach emphasizes individual learning trajectories, multimodal content delivery, and personalized feedback mechanisms to foster communicative competence in English. By integrating educational psychology, assistive technology, and language pedagogy, this work provides a model for creating sustainable and inclusive English language learning environments in home education contexts.